The Effectiveness of Autogenic Relaxation Therapy in Reducing Anxiety and Pain in Patients with Acute Myocardial Infarction: A Literature Review - Ni Luh Putu Yudi Apriani; Ni Luh Putu Inca Buntari Agustini; Israfil Israfil; Anak Agung Istri Wulan Krisnandari (Indonesian Journal of Global Health Research, 2026)
Autogenic Therapy (AT) is a relaxation technique widely used for stress and anxiety reduction, pain management, and psychological well-being. However, variations in its duration, frequency, and effectiveness across different populations remain unclear. Objective: This review aims to synthesize the available evidence on AT’s impact on psychological well-being and chronic pain management. A systematic review was conducted on studies evaluating AT interventions across different populations, including healthy individuals, cardiovascular patients, stroke survivors, cancer patients, individuals with chronic pain and type 2 diabetes, and those affected by crises. Data on intervention duration, session frequency, and health outcomes were extracted and analyzed. Findings indicate that AT interventions range from one week to several months, with session frequencies between two and five times per week. Short-term programs (1–4 weeks) are common in perioperative settings, while medium-term programs (6–12 weeks) are typically used for patients with cardiovascular, neurological, or diabetic conditions. Long-term interventions (≥12 weeks) are preferred for chronic pain and general anxiety. Higher session frequencies correlate with greater psychological and physiological benefits. AT is an effective intervention across diverse populations, but its efficacy is influenced by intervention length and session frequency. Tailored programs based on patient needs and conditions may enhance therapeutic outcomes. Future research should standardize protocols to optimize AT effectiveness.